Enhancing the performance of cascaded three-level VSC STATCOM by ANN controller with SVPWM integegration - Mohamad Milood Almelian; Izzeldin. I. Mohd; Abu Zaharin Ahmad; Mohamed Salem; Mohamed A. Omran; Awang Jusoh; Tole Sutikno (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This article presents a cascaded three-level voltage source converter (VSC) based STATCOM employing an artificial neuron network (ANN) controller with a new simple circuit of space vector pulse width modulation (SVPWM) technique. The main aim of utilizing ANN controller and SVPWM technique is to minimize response time (RT) of STATCOM and improve its performance regard to PF amplitude, and total harmonic distortion (THD) of VSC output current during the period of lagging/leading PF loads (inductive/capacitive loads). The performance of STATCOM is tested using MATLAB/SIMULINK in IEEE 3-bus system. The simulation results clearly proved that the STATCOM with intelligent controller is more efficient compared to a conventional controller (PI controller), where ANN enables the voltage and current to be in the same phase rapidly (during 1.5 cycles) with THD less than 5%.